2018
DOI: 10.1155/2018/1624520
|View full text |Cite
|
Sign up to set email alerts
|

A New Model-Free Trajectory Tracking Control for Robot Manipulators

Abstract: In this paper, we propose a novel model-free trajectory tracking control for robot manipulators under complex disturbances. The proposed method utilizes time delay control (TDC) as its control framework to ensure a model-free scheme and uses adaptive nonsingular terminal sliding mode (ANTSM) to obtain high control accuracy and fast dynamic response under lumped disturbance. Thanks to the application of adaptive law, the proposed method can ensure high tracking accuracy and effective suppression of noise effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(113 reference statements)
0
4
0
Order By: Relevance
“…When designing a profile to control robotic arm movement, operators typically define the motion path [16]. Control in such programs encompasses point-topoint control and trajectory tracking control, each with distinct advantages and disadvantages [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…When designing a profile to control robotic arm movement, operators typically define the motion path [16]. Control in such programs encompasses point-topoint control and trajectory tracking control, each with distinct advantages and disadvantages [17], [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the design of a motion profile to control the movement of robotic arms, the operator must define the motion path as the movement of a robotic arm. In the control of a program, there will be a point-to-point control [23] and trajectory tracking control [24], [25], in which each control has different advantages and disadvantages. The repetitive process [26] is part of the robot's control to do the same thing again.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation result of two-link robot showed that the proposed method was effective [2]. A novel model free trajectory tracking control algorithm for robot manipulators under complex disturbances was proposed by Wang et al, which uses time delay control (TDC) as the control model to ensure a model-free plan and the utilization of the adaptive nonsingular terminal sliding mode (ANTSM) to gain high control accuracy and fast dynamic response under lumped disturbance [3].…”
Section: Introductionmentioning
confidence: 99%